Efektivitas Media Eco-Canva untuk Meningkatkan Pemahaman Siswa Terhadap Sikap Peduli Lingkungan di Sekolah Dasa - Imas Stiawati; Irfan Fajrul Falah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effectiveness of Eco-Canva media in improving students' understanding of environmental care attitudes in Pancasila Education learning for grade III of Haurkuning Public Elementary School. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research sample consisted of 52 students, namely 26 students of grade III A as the experimental group and 26 students of grade III B as the control group selected using a purposive sampling technique. Data were collected through a multiple-choice test of 20 questions and a student response questionnaire. Data analysis was carried out using descriptive statistics, normality tests, homogeneity tests, Independent Sample t-Tests, and N-Gain Score tests. The results showed that the average score of the experimental group increased from 76.73 in the pretest to 90.38 in the posttest, while the control group increased from 73.46 to 78.85. The results of the hypothesis test showed a significance value of 0.000 <0.05, so there was a significant difference between the two groups. The N-Gain value of 58.97% is categorized as quite effective, while student responses to Eco-Canva media are categorized as good. Thus, Eco-Canva media is quite effective as an alternative learning medium for Pancasila Education to improve students' understanding of environmental stewardship.